A unique combination of rare mitochondrial ribosomal RNA variants affects the kinetics of complex I assembly. (June 2016) - Porcelli, Anna Maria; Calvaruso, Maria Antonietta; Iommarini, Luisa; Kurelac, Ivana; Zuntini, Roberta; Ferrari, Simona; Gasparre, Giuseppe
Abstract: Mitochondrial DNA (mtDNA) mutations in respiratory complexes subunits contribute to a large spectrum of human diseases. Nonetheless, ribosomal RNA variants remain largely under-investigated from a functional point of view. We here report a unique combination of two rare mitochondrial rRNA variants detected by serendipity in a subject with chronic granulomatous disease and never reported to co-occur within the same mitochondrial haplotype. In silico prediction of the mitochondrial ribosomal structure showed a dramatic rearrangement of the rRNA secondary structure. Functional investigation of cybrids carrying this unique haplotype demonstrated that the co-occurrence of the two rRNA variants determines a slow-down of the mitochondrial protein synthesis, especially in cells with an elevated metabolic rate, which impairs the assembly kinetics of Complex I, induces a bioenergetic defect and stimulates reactive oxygen species production. In conclusion, our results point to a sub-pathogenic role for these two rare mitochondrial rRNA variants, when found in the unique combination here reported in a single individual.